Brain structure and function: a multidisciplinary pipeline to study hominoid brain evolution - Friederici, Angela D.; Wittig, Roman M.; Anwander, Alfred; Eichner, Cornelius; Gräßle, Tobias; Jäger, Carsten; Kirilina, Evgeniya; Lipp, Ilona; Düx, Ariane; Edwards, Luke J.; Girard-Buttoz, Cédric; Jauch, Anna; et al. (Frontiers in Integrative Neuroscience, 2024)
To decipher the evolution of the hominoid brain and its functions, it is essential to conduct comparative studies in primates, including our closest living relatives. However, strong ethical concerns preclude in vivo neuroimaging of great apes. We propose a responsible and multidisciplinary alternative approach that links behavior to brain anatomy in non-human primates from diverse ecological backgrounds. The brains of primates observed in the wild or in captivity are extracted and fixed shortly after natural death, and then studied using advanced MRI neuroimaging and histology to reveal macro- and microstructures. By linking detailed neuroanatomy with observed behavior within and across primate species, our approach provides new perspectives on brain evolution. Combined with endocranial brain imprints extracted from computed tomographic scans of the skulls these data provide a framework for decoding evolutionary changes in hominin fossils. This approach is poised to become a key resource for investigating the evolution and functional differentiation of hominoid brains.